Hearts2Hearts Brand Ambassador Influence and Consumer Repurchase Intention: A Study of Scarlett Product Users in Jayapura City - Indra Eka Wardana Toii; Xenia Irene Sandy Landjang (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to examine the influence of the Hearts2Hearts brand ambassador on repurchase intention among Scarlett product consumers in Jayapura City. The use of brand ambassadors has become a key marketing strategy in strengthening consumer perceptions and encouraging repeat purchases, particularly in the skincare and beauty industry. This research employed a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to Scarlett product users in Jayapura City. The sampling technique applied was purposive sampling, targeting respondents who have purchased Scarlett products and are aware of Hearts2Hearts as the brand ambassador. Data analysis was conducted using SmartPLS 4.0 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The measurement model was evaluated through validity and reliability testing, including convergent validity, discriminant validity, composite reliability, and Cronbach’s alpha. Furthermore, the structural model was assessed by analyzing path coefficients and hypothesis testing. The results reveal that the Hearts2Hearts brand ambassador has a positive and significant effect on consumer’s repurchase intention toward Scarlett products in Jayapura City. This indicates that an effective brand ambassador contributes to stronger consumer confidence and increased intention to repurchase. The findings provide practical implications for marketers in optimizing brand ambassador strategies to enhance consumer loyalty and strengthen market competitiveness.